(untitled) (Ticontre. Teoria Testo Traduzione, 2020)
In his essay A Dwelling in the Kingdom of Shadows (Odna iz obitelej carstva tenej, 1924), the symbolist writer Andrej Belyj reflects upon his experience in Berlin (1921-1923). Astonished by the cultural ibridism that permeates the German capital – fallen pray at the same time to the Russian émigrés and to the penchant for exoticism – the author describes the grotesque mixture of different cultural codes coexisting within the same society. The article analyses Belyj’s point of view towards the penetration of ‘alien’ cultural codes into the European one; furthermore, it underlines the syncretic techniques used by the author to convey on a formal level the cultural ibridism seen in Berlin. In the following analysis Jurij Lotman’s theory on the text within a text and Renate Lachmann’s studies on intertextuality in Russian modernism will be taken into account.